2018
DOI: 10.1016/j.cmi.2017.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical course of Clostridium difficile infection in glutamate dehydrogenase-positive toxin-negative patients diagnosed by PCR to those with a positive toxin test

Abstract: Objectives: To evaluate the potential role of PCR-based assays in the over-diagnosis of Clostridium difficile infection (CDI) by using a validated diagnostic algorithm in daily clinical practice. Methods: We performed a retrospective cohort study evaluating all C. difficile-positive stool samples identified at our institution during a 12-month period, to compare outcomes and recurrence rates between patients with a positive enzyme immunoassay (EIA) for both glutamate dehydrogenase (GDH) and toxin A/B ('toxin-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
27
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
(13 reference statements)
6
27
3
Order By: Relevance
“…Our results differ from studies of general medical patients that have found those with toxin EIA(+) C. difficile results to have both a greater prevalence of CDI clinical characteristics and worse outcomes compared to PCR (+)/EIA (−) results 7,8 . A prospective study without GDH screening found those with PCR (+)/EIA (−) results to have a lower prevalence of leukocytosis, fewer number of stools, and lower rates of adverse outcomes, including mortality and recurrent CDI 7 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from studies of general medical patients that have found those with toxin EIA(+) C. difficile results to have both a greater prevalence of CDI clinical characteristics and worse outcomes compared to PCR (+)/EIA (−) results 7,8 . A prospective study without GDH screening found those with PCR (+)/EIA (−) results to have a lower prevalence of leukocytosis, fewer number of stools, and lower rates of adverse outcomes, including mortality and recurrent CDI 7 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, the 30-day mortality of 0.6% in the PCR (+)/EIA (−) group in this study compared to 15% in our study highlights the significant difference in study populations. Another recent study also demonstrated higher rates of leukocytosis, fever, and severe CDI as well as recurrent C.difficile infection with an EIA(+) result versus PCR (+)/EIA (−) result after GDH screening, but did not find a difference in mortality between the groups 8 . Notably, our study included only samples collected through routine clinical care and were tested via a multistage process which included a C.difficile GDH screening test.…”
Section: Discussionmentioning
confidence: 89%
“…In a recently published retrospective cohort study (8), we found that both the occurrence of severe or complicated forms of CDI and recurrence were significantly more common among patients with a positive EIA for both GDH and toxin A/B than among those with GDH-positive, toxin-negative samples for whom the diagnosis of CDI was made by a positive PCR-based assay. In the present study, our aim was to evaluate if toxin B PCR C T adds something to the combination of clinical variables and free toxin detection by EIA in predicting recurrence or a poor CDI outcome.…”
mentioning
confidence: 80%
“…Episodes of CDI without adequate information were excluded, as well as those without a traceable 8-week follow-up after the end of treatment and those for which the C T result for the tcdB PCR was not available. More details about the cohort on which the present study is based are described elsewhere (8). The local clinical ethics committee approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation